Gastro-intestinal transit time in South American deer - de Oliveira, L. D.; Duarte, JMB (Wiley-Blackwell, 2006)
The study of diet and physiological peculiarities of the digestive system of neotropical deer is not well known and the literature shows inconsistencies. To better understand the digestive system of these mammals the difference in the gastro-intestinal transit time of four species of neotropical deer (Mazama americana, Mazama gouazoubira, Mazama nana, Blastocerus dichotomus), kept ill captivity, was evaluated. Four plants (Neonotonia wightii, Morus albans, Medicago sativa, Leucaena leucocephala) were utilized and two variables were measured, mean time of the beginning of the elimination (BE) and mean time of permanence (TP). The results obtained for BE indicated similarity among the deer species, with significant differences between M. gouazoubira (mean = 13.62 hr) and M. Americana (mean = 19.25 hr). For the plants, the BE was faster with N. wightii and L. leucocephala, and slower for M. sativa. The TP results for B. dichotomus showed longer time when compared to the other species, whereas M. gouazoubira had a lower permanence. Overall, N. wightii had the highest retention time in the digestive tract of all the deer species studied. Associated with this observation, N. wightii had the highest quantity of plant fiber of the plants tested. In a similar fashion M. sativa showed the lowest TP in the digestive tract of the deer and had the lowest quantity of acid detergent fiber. The data from this study showed that, within species, the shape of the excretion curve of the plants was similar when the animals consumed N. wightii or M. sativa. Blastocerus dichotomus and M. gouazoubira had the highest and the lowest gastro-intestinal transit time, respectively. This suggests that these species characterize different abilities to digest high fiber food, and consequently, represent the two extremities in the morphophysiological adaptation within the deer species evaluated. This information is vital because it is important to know the digestive physiology to define the diet of captive animals, particularly regarding the quantity and quality of fiber. Zoo Biol 25:47-57, 2006. (C) 2005 Wiley-Liss, Inc.
Keywords: Cervidae; digestive system; Mazama; Blastocerus dichotomus; microhistology